World Heritage Rescue of Sewell Mining Campsite in Chile - Ravinet, F. (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
Sewell is closely associated with El Teniente, the largest underground copper mine in the world, owned by the State of Chile and located amidst the High Andes, 150 km to the south of Santiago, Chile. Since 2006, Sewell has been recognized as a UNESCO World Heritage Site, because “ in its hostile environment, it is an exceptional example of the global phenomena of ‘company towns’ established in remote parts of the world, through a fusion of local labor with resources from already industrialized nations.” The aim of this paper is to illustrate the significance of the Sewell Mining Campsite, and to describe the strategy, actions and achievements of Codelco Chile, in the world heritage rescue process.